THE EXPERIMENT OF INTEGRATING SERVICE-LEARNING AND CLASSROOM INSTRUCTION IN AN ARCHITECTURAL DESIGN STUDIO THROUGH PARTICIPATION: THAILAND - Pimwern, Tirawat (International Journal of Psychosocial Rehabilitation, 2020)
Integrated instruction is a critical approach to Thailand’s education. Several universities try to promote and implement this approach in curricula. This approach could help students become more engaged in class; additionally, students can use multiple skills to solve social problems. Notably, integrated instruction has a significant impact on academic services for local communities. This learning approach is not widely implemented in Thailand’s curricula currently. This research aims to examine the potential implementation of integrated instruction in an architectural design studio using a research-based approach. There are 100 participants including community-members, architectural design students, and instructors in this research. The results show that utilizing research integration in education is a new approach for Thai architectural curriculum and the pedagogical approach is not well integrated in the research methodology. To achieve integrated instruction using the cohesive research process, it is suggested that 1] the researcher should clearly understand both the class curriculum and the research objectives, 2] the class schedule and the research timeline should be well integrated, and 3] the class schedule, learning methodologies, and tools should be flexible and adjusted for unexpected occurrences. Finally, this paper could offer a useful guideline for implementing improved teaching performance by integrating service–learning and classroom instruction in an architectural design project.